The Holy Spirit and time in contemporary Catholic and Protestant theology - Vondey, Wolfgang (Scottish journal of theology, 2005)
Contemporary Catholic and Protestant theology has transposed the scientific debate on time into an eschatological discussion about subjective time and objective time. This discussion can be made intelligible in the context of modern cosmology if we allow contemporary eschatology to be transformed by a pneumatological approach to time. In the self-giving of the Holy Spirit into time, the ‘wheel of history’ is identical with the eschatological arrow of history. This is exemplified in a theology of the cross which locates the eternal power of the cross not in the human act of anamnesis by recalling in the present Christ's sacrifice as an event of the past, but in the Holy Spirit who liberates Christ's historical sacrifice on the cross from its temporal coordinates and propels the redemptive act throughout time towards any person in history. A pneumatological approach to time suggests that eschatology is determined not only by the end and the consummation of the present in the future but also by the perpetuation of the present moment through the power of God unfolding in time in the operation of the Holy Spirit. If it can be shown that this is true not only for a theology of the cross, then it may be possible to say, in general, that the unique finality and collective character of God's work of salvation at any moment in history is made possible by the perpetuating work of the Holy Spirit as the eternal lord of time and history.